Intestinal microbiota in children with bronchial asthma - T. S. Sokolova; V. N. Malchuk; O. S. Fedorova; V. V. Kulenich; V. E. Odintsova; S. I. Koshechkin (Бюллетень сибирской медицины)
Background. Intestinal microbiota is one of the most important factors determining the state of human health, including its influence on the immunological mechanisms regulating the development of allergic diseases in childhood. The role of intestinal microbiota and the gut – lung axis in the development of bronchial asthma (BA) is an important area of research.Aim. To analyze the taxonomic composition of intestinal microbiota in children with BA using 16S rRNA gene sequencing.Materials and methods. The study included patients with BA (n = 50, mean age 10.34 ± 2.99 years) and a group of apparently healthy individuals (n = 49, mean age 10.3 ± 2.8 years). For all patients, medical history was taken, and physical examination and stool test were performed. Patients with BA were assessed for the level of total and specific immunoglobulin (Ig) E and underwent spirometry. The microbiota composition was analyzed by 16S rRNA gene sequencing with subsequent bioinformatic and statistical analysis.Results. Significant differences in the composition of the intestinal microbiota (beta diversity) and a decrease in taxonomic diversity (alpha diversity) were found in patients with BA compared to healthy controls. The intestinal microbiota of patients with BA was characterized by an increase in the abundance of Bacteroides, Parabacteroides, Lachnospira, Roseburia, Akkermansia, Anaerostipes, Sutterella, Odoribacter, Phascolarctobacterium, Butyricimonas, as well as unclassified bacteria from the Rikenellaceae families. The intestinal microbiota of children without BA was characterized by greater abundance of bacteria from Blautia, Bifidobacterium, Dorea, Ruminococcus, Streptococcus, Eubacterium, Acinetobacter, Collinsella, Lactococcus, Catenibacterium genera and unclassified bacteria from the Clostridiaceae and Coriobacteriaceae families. Significant differences in the quantitative abundance of bacteria were revealed depending on the type of sensitization, the level of total IgE, and the value of FEV1.Conclusion. The results obtained indicate the differences in the intestinal microbiota composition in children with BA and healthy children.